Body mass estimation from knee breadth, with application to early hominins. Issue 2 (14th July 2015) - Squyres, Nicole; Ruff, Christopher B.
Abstract Objectives The estimation of living body mass from skeletal dimensions is an important component of many studies of early hominins and more recent human archaeological remains. Most previous investigations have concentrated on weight‐bearing elements of the lower limb, in particular the femoral head. In this study, we develop new body mass estimation equations derived from measurements of the knee in a modern sample of known body mass, and use them to estimate body mass in 11 fossil hominin specimens (including Au. africanus, Au. afarensis, and early Homo). Materials and Methods The reference sample consisted of 100 living subjects who participated in the Baltimore Longitudinal Study of Aging. Mediolateral breadth measurements were taken from radiographs of the knee, and regressed against recorded body weight to generate body mass estimation equations. Results Knee dimensions were generally found to be good predictors of body mass in the modern human sample, with median absolute percent prediction errors of 7 to 9% (comparable to or better than previously reported equations derived from the femoral head). Taxon‐average estimated body masses were 46.1 kg for Au. afarensis, 38.4 kg for Au. africanus, and 53.6 kg for early Homo. Discussion Estimates for early Homo were similar to or smaller than those generated previously from the femoral head. Estimates for australopiths, however, were larger than those generated from femoral head equations. This result is consistent with other evidence that the femoral head was relatively unloaded in australopiths compared with Homo, possibly due to subtle differences in gait. Am J Phys Anthropol 158:198–208, 2015. © 2015 Wiley Periodicals, Inc.